Dentoalveolar Heights in Skeletal Malocclusion: A Dual Plane Study - Yadav, Rajiv; Joshi, Deepak Raj; Yadav, Neelam; Yadav, Anil (Journal of Institute of Medicine Nepal, 2025)
Introduction Skeletal malocclusions are manifested in sagittal, vertical and transverse discrepancies. Aim of this study was to determine the relationship of dentoalveolar heights among skeletal malocclusion with different growth patterns.MethodsIn this cross-sectional study, traced cephalometric X-rays were grouped into skeletal Class I, Class II, Class III based on Steiner’s ANB angle and growth patterns based on Steiner’s SN-GoGn Angle and Tweeds FMA angle. A Total of 180 samples were proportionally divided in nine groups based on growth pattern and malocclusion classification. ANOVA was applied for data analysis using SPSS V21.ResultsUpper anterior dental height (UADH) showed significance differences in all three planes, (Class I: p=0.041, Class II: p=0.043, Class III: p=0.013),  Lower anterior dental height (LADH) showed no statistically significant differences across any class of malocclusion (all p > 0.1). In UADH, Class I and III exhibited lower values in horizontal compared to normal, while Class I and II showed lower UADH in vertical compared to horizontal. For UPDH, Class III showed lower values in vertical compared to normal, whereas Class II and III showed lower UPDH in vertical compared to horizontal. In LPDH, a significant reduction was found in Class III individuals with vertical patterns compared to horizontal.ConclusionSignificant differences were mainly observed between horizontal and vertical growth patterns in Class II and III. In class I, differences were notable between normal to horizontal and horizontal to vertical growth patterns.